2021
DOI: 10.1038/s41598-021-81755-x
|View full text |Cite
|
Sign up to set email alerts
|

Application of response surface methodology on the nanofluid flow over a rotating disk with autocatalytic chemical reaction and entropy generation optimization

Abstract: The role of nanofluids is of fundamental significance in the cooling process of small electronic devices including microchips and other associated gadgets in microfluidics. With such astounding applications of nanofluids in mind, it is intended to examine the flow of magnetohydrodynamic nanofluid comprising a novel combination of multi-walled carbon nanotubes and engine oil over a stretched rotating disk. The concentration equation is modified by considering the autocatalytic chemical reaction. The succor of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(13 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…Related studies are traced in. [68][69][70] Here in the study, an unsteady, thermally radiative magnetized water-based hybrid nanoliquid with graphene and ferrous oxide over a revolving slippery disk is investigated. The nonlinear leading equations after reducing to ordinary differential equations (ODEs) by proper similarity transform; the RK-4 shooting technique is introduced to unravel the system, and the simulation is performed via MPLE-2018 software.…”
Section: Introductionmentioning
confidence: 99%
“…Related studies are traced in. [68][69][70] Here in the study, an unsteady, thermally radiative magnetized water-based hybrid nanoliquid with graphene and ferrous oxide over a revolving slippery disk is investigated. The nonlinear leading equations after reducing to ordinary differential equations (ODEs) by proper similarity transform; the RK-4 shooting technique is introduced to unravel the system, and the simulation is performed via MPLE-2018 software.…”
Section: Introductionmentioning
confidence: 99%
“…Box and Wilson’s Response Surface Methodology (RSM) is a feasible approach in experimental design for proper observation of the mechanism and computing the values of input parameters that optimize the response. Different studies using RSM have been done; a few of them can be seen in 48 – 52 and in their references. Researchers can utilize RSM to help them create a list of experimental designs which can be used to predict response.…”
Section: Introductionmentioning
confidence: 99%
“…Most of these studies were focused towards the experimental or numerical investigations on the use of nanofluids for improved performance of stationary pipes with meshes, pipe at different inclinations, and stationary thermosyphons etc., but rotating heat pipes have received very less attention. Apart from this, it is also observed that none of the numerical studies done so far has given any insight about the sensitivity of involved nanofluid and heat pipe parameters on the heat transfer performance of rotating heat pipe like the investigation done by Mehmood et al 38 , where the authors utilized an statistical technique to fit a regression model for identifying the important parameters influencing the flow of a nanofluid over rotating disk. Recently, Li et al 39 presented a comprehensive and comparative review on the numerical and experimental studies of different types of rotating heat pipes.…”
Section: Introductionmentioning
confidence: 99%